Seismic behavior and damage evolution for retrofitted RC frames using haunch viscoelastic damping braces. (15th November 2019) - Dong, Yao-Rong; Xu, Zhao-Dong; Li, Qiang-Qiang; Xu, Ye-Shou; Chen, Zheng-Han
Highlights: An advanced frame structure system retrofitted by adding haunch viscoelastic damping braces is presented. The seismic behavior and rebar strain at key locations of CFs and VFs are discussed. A comparative study on the damage evolution about two types of frames at the material scale is carried out. The addition of HVEDB guarantees the seismic design requirements of "strong nodes and weak components. Abstract: To upgrade the existing RC frame structure system with insufficient seismic design and improve the seismic design of the RC frame structures, a novel and advanced frame structure system retrofitted by adding haunch viscoelastic damping braces (HVEDB) is presented in this study based on the good energy dissipation performance, the low-cost and non-invasive addition of viscoelastic dampers. For a comprehensive and systematic research of this new structure system, the seismic behavior of ten RC frames and another ten RC frames added by HVEDB with the axial load ratio (ALR) of 0.1–1.0 are carried out under horizontal sinusoidal steady-state excitation loading, including the hysteretic behavior, load-bearing capacity, stiffness degradation, energy dissipation capacity, additional damping ratio and rebar strain at key locations. On this basis, four reasonable damage indicators at the material scale are proposed, and a comparative study on the damage evolution about two types of frames at the material scale in the whole process is carried out. The study results show that the addition of HVEDB can greatly improve the seismic performance such as load-bearing capacity, lateral stiffness, deformation capability and energy dissipation, and it changes the failure mode of the RC frames. The HVEDB can provide the effective protection for the beam-column joints by transferring the damage region from the beam-column joint to the frame beam successfully, which guarantee the seismic design requirements of "strong nodes and weak components" avoiding the brittle failure mode of frame structure under high ALR.